The Effect of Technological Innovation on Employee Performance in Pandemic Era: Case from Banking Industry in Indonesia - Prasetyaningtyas, Sekar Wulan; Aishah, Aishah; Hansen, Brenda; Kuspriandani, Deviana (LPPM Universitas Terbuka, 2021)
This study assessed the impact of technological innovation on employee performance, especially during the COVID-19 pandemic situation. Data were gathered from private and government banks that applied technological innovations to the COVID-19 Pandemic. The author also elucidated more about the influence of technological innovation on employee performance, influenced by job satisfaction, work-life balance, and burnout. This study described technological innovation within the Jabodetabek Area’s banking industry by using variables that affect employee performance. The questionnaires were distributed through social media to 123 respondents under 40 years of work. The data were then analyzed using PLS-SEM through SmartPLS 3 software. Findings. The results of this study indicated the positive effect of technological innovation on the performance of bank employees. Utilizing technological innovation will increase employees’ satisfaction at work, balance employees' lives, reduce burnout, and improve employee performance eventually. This paper focused on the variables used in the banking industry, especially in COVID-19 Pandemic. Mediating variables used also have never been explored in the previous research.